Windows store app development C♯ and XAML - Brown, Pete (Manning, 2013)
Annotation
Print version record
Keywords: Application software -- Development; Document markup languages; C# (Computer program language); Logiciels d'application; Développement; Langages de balisage; C# (Langage de programmation); Application software; Development; Engineering & Applied Sciences; Computer Science